Semeadura direta na restauração em floresta tropical úmida na Colômbia - Marin Paladines, Harvey (Universidade Federal de São Carlos, 2022)
Faced with the challenges of ecological restoration, the study of techniques that can be used on a large scale, with cost reduction and efficiency of results, direct sowing has shown success in several places, requiring improvement of the methodology and, mainly, selection of species. suitable for use at the beginning of the restoration implementation. Thus, our objectives were to identify forest species with aptitude for direct seeding as well as to analyze survival and development, according to their performance in the variables studied in order to classify the species based on their probability of success and potential for direct seeding. In an area of 768 m2 in the municipality of Popayán – Cauca, Colombia, direct sowing was implemented, in a row system, using manual sowing in a row, compared to manual sowing by hauling in soil prepared by harrowing where 17 forest species of different families and sizes were used. with a density of 250,000 seeds.ha-1. Emergence was monitored for 450 days at different intervals and all individuals were identified and marked in 64 plots of 3m x 2m. Height (H) and diameter at neck height (DAC) were counted and measured for all seedlings. Potential classes were established based on their growth (H, DAC), germinability, emergence and probability of success. 94.12% (16 species) emerged with 5 to 240 individuals, and 1024 survivors after 450 days (13,333 plants.ha-1). Germinability (Gd) and survival rate (S) were significant predictors of Probability of Success (PBS) in the linear regression model built, there was a tendency to increase Probability of success with increasing Germinability (Gd) and survival rate (S). Principal Component Analysis (PCA) showed that the first two components were responsible for 77.4% of the total variance of the data set; additionally, a strong correlation was observed between the variables PBS (Probability of success), Gd (Germinability), survival (S) with the large and medium sizes of seeds regardless of the ecological group. It can be concluded that the non-pioneer species, Inga densiflora, Quercus. humboldtii and Jacaranda caucana; as well as the pioneer species Delostoma integrifolium and Heliocarpus americanus showed the best aptitude and at the same time correlation with the variables Probability of success, Germinability, survival, Emergence and growth in height and diameter.
Direct sowing in tropical rainforest restoration in Colombia
Keywords: Seleção de espécies; Áreas degradadas; Muvuca de sementes; Sementes florestais; Species selection; Degraded areas; Seed mix; Forest seeds; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL